EVALUATION OF SAFETY OF BIPOLAR DIATHERMY TONSILLECTOMY - Shah, Shahid Ali; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2007)
Background: Tonsillectomy is a common operation in both children as well as adults, performed by a variety of techniques that have evolved over the years to ensure the safety of the procedure. Cold dissection and electrodissection are the two mostly used techniques. Bipolar diathermy tonsillectomy was evaluated for its safety and postoperative morbidity. Methods: This study was conducted over a period of two years, in the Department of Ear, Nose Throat and Head & Neck Surgery at Ayub Teaching Hospital, Abbottabad, Pakistan. Two hundred and forty-six were enrolled; however, 238 patients completed the full evaluation as the technique had to be modified in 8 patients. All the procedures were performed by the first author thereby ensuring the same expertise level. Operating time, intraoperative blood loss, postoperative algesia, feeding status and time taken getting back to school/work and episodes of secondary bleeding were recorded. Results: Time taken by the procedure ranged from 10 to 20 minutes. Intraoperative blood loss ranged between 2 to 5 ml. Postoperative pain averaged around 3-5 on a 1-10 point scale in 75% of patients. 80% of patients were back to normal diet by day 3 postoperative. Nine (3.6%) patients had a secondary haemorrhage that was managed conservatively and did not need surgical intervention. Conclusion: Bipolar diathermy tonsillectomy is an effective and safe technique, especially in children population. Adequate experience with the technique is mandatory to achieve the desired goals. Keywords: Tonsillectomy; Electro dissection; Bipolar diathermy; Morbidity